2019
DOI: 10.1038/s41467-019-09636-6
|View full text |Cite
|
Sign up to set email alerts
|

MKL1-actin pathway restricts chromatin accessibility and prevents mature pluripotency activation

Abstract: Actin cytoskeleton is well-known for providing structural/mechanical support, but whether and how it regulates chromatin and cell fate reprogramming is far less clear. Here, we report that MKL1, the key transcriptional co-activator of many actin cytoskeletal genes, regulates genomic accessibility and cell fate reprogramming. The MKL1-actin pathway weakens during somatic cell reprogramming by pluripotency transcription factors. Cells that reprogram efficiently display low endogenous MKL1 and inhibition of actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 64 publications
3
35
0
Order By: Relevance
“…Indeed, when we FACS sorted cells based on forward scatter alone, a crude measure of cell size, and compared their reprogramming efficiency, smaller cells indeed displayed higher reprogramming activity (Figures 4B-C). Such observation is consistent with our previous finding that reprogramming requires reduced MKL1/SRF activity (Hu et al, 2019).…”
Section: Caglow Cells Are Small In Size With Reduced Srf Target Genessupporting
confidence: 94%
See 2 more Smart Citations
“…Indeed, when we FACS sorted cells based on forward scatter alone, a crude measure of cell size, and compared their reprogramming efficiency, smaller cells indeed displayed higher reprogramming activity (Figures 4B-C). Such observation is consistent with our previous finding that reprogramming requires reduced MKL1/SRF activity (Hu et al, 2019).…”
Section: Caglow Cells Are Small In Size With Reduced Srf Target Genessupporting
confidence: 94%
“…We examined whether CAG:H2B-GFP intensity decreases during early reprogramming to reflect the decreasing MKL1/SRF activity (Hu et al, 2019). Shortly after Dox addition, there was a marked down-regulation of CAG:H2B-GFP intensity within the mCherry+ population ( Figures 1B-C), consistent with reduced activity of MKL1/SRF.…”
Section: Cells Expressing Low Cag Promoter Activity Emerge During Earmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that low actin cytoskeleton is critical for the maturation of reprogramming fibroblasts. Elevated actin cytoskeleton by sustained MKL1 activity potently restricts nuclear dynamics, reduces chromatin accessibility, and inhibits pluripotency activation, partly through constricting the nuclei via the linker of nucleoskeleton and cytoskeleton complex . This work depicts a novel perspective on how cell cycle could regulate cell fate and demonstrates how a ubiquitous structural network could regulate nuclear dynamics and control cell fate.…”
Section: Potential Molecular Consequences Of Rapid Cell Cyclementioning
confidence: 85%
“…In the fibroblast reprogramming model, dramatic downregulation of the actin cytoskeleton occurs as cells undergo this fate transition [100,101]. The systematic reduction of the actin cytoskeletal network is caused by reduced activity of the transcription factors megakaryoblastic leukemia-1/serum response factor (MKL1/SRF) [101]. Hu et al demonstrated that low actin cytoskeleton is critical for the maturation of reprogramming fibroblasts.…”
Section: Heightened Chromatin Accessibility From a Weakened Actin Cytmentioning
confidence: 99%